Next‐Generation Sequencing Reveals Restriction and Clonotypic Expansion of Treg Cells in Juvenile Idiopathic Arthritis. Issue 7 (July 2016) - Henderson, Lauren A.; Volpi, Stefano; Frugoni, Francesco; Janssen, Erin; Kim, Susan; Sundel, Robert P.; Dedeoglu, Fatma; Lo, Mindy S.; Hazen, Melissa M.; Beth Son, Mary; Mathieu, Ronald; Zurakowski, David; et al.
Abstract : Objective: Treg cell–mediated suppression of Teff cells is impaired in juvenile idiopathic arthritis (JIA); however, the basis for this dysfunction is incompletely understood. Animal models of autoimmunity and immunodeficiency demonstrate that a diverse Treg cell repertoire is essential to maintain Treg cell function. The present study was undertaken to investigate the Treg and Teff cell repertoires in JIA. Methods: Treg cells (CD4+CD25+CD127 low ) and Teff cells (CD4+CD25−) were isolated from peripheral blood and synovial fluid obtained from JIA patients, healthy controls, and children with Lyme arthritis. Treg cell function was measured in suppressive assays. The T cell receptor β chain ( TRB ) was amplified by multiplex polymerase chain reaction and next‐generation sequencing was performed, with amplicons sequenced using an Illumina HiSeq platform. Data were analyzed using ImmunoSEQ, International ImMunoGeneTics system, and the Immunoglobulin Analysis Tools. Results: Compared to findings in controls, the JIA peripheral blood Treg cell repertoire was restricted, and clonotypic expansions were found in both blood and synovial fluid Treg cells. Skewed usage and pairing of TRB variable and joining genes, including overuse of gene segments that have been associated with other autoimmune conditions, was observed. JIA patients shared a substantial portion of synovial fluid Treg cell clonotypes that were private to JIA and not identified in Lyme arthritis. Conclusion: We identified restriction and clonotypic expansions in the JIA Treg cell repertoire with sharing of Treg cell clonotypes across patients. These findings suggest that abnormalities in the Treg cell repertoire, possibly engendered by shared antigenic triggers, may contribute to disease pathogenesis in JIA.